A New Stage of Afghan Crisis and U.S. Strategy Options - N. I. Shapiro (Международная аналитика, 2017)
This article explores the evolution of the U.S. policy towards Afghanistan between 2009-2017 with particular emphasis on major adjustments to the original plans outlined by President Obama. The article analyses the main reasons underlying contraction of foreign policy decision-making cycles during Obama’s second term. It examines regional dynamics and the new developments in Afghanistan primarily the Taliban’s dramatic gains and the Islamic State’s growing presence since the official end of the coalition’s combat mission. It also analyzes the continuity and change aspects of Donald Trump’s new strategy in Afghanistan and South Asia.